THE EFFECTIVENESS OF HIIT TRAINING IN ENHANCING NEUROMUSCULAR EFFICIENCY AND DEVELOPING THE BLOCKING SKILL IN VOLLEYBALL PLAYERS - Dr. Ahmed Wahan Hamid (Proximus Journal Publishing, 2025)
Since the research problem is best addressed by the experimental method, the researcher took this approach. The sample of the study was intentionally chosen against the backdrop of senior volleyball players in the province of Diyala and distributed among 4 sports clubs. The main sample, which consisted of players from Khanqin Sports Club and Al-Wajihiya Sports Club, was randomly selected with the lottery method. The sample was split into two: experimental and control. 18 players from Khanqin Club and 14 players from AlWajihiya Club. The results of the study showed statistically significant differences in neuromuscular efficiency between groups, with the experimental group undergoing HIIT training performing better than controls. This result is a proof of the effectiveness of this type of training in provoking neuromuscular adaptations of volleyball players. In addition, HIIT training had a clear influence on motor skills associated with rapid and explosive movement, as well as precise neuromuscular coordination.
Keywords: HIIT Training Effectiveness; Neuromuscular Efficiency; Volleyball